Optimization Of Digital Recording as A Performance Monitoring Tool for Non-Civil Servant Human Resources in Kediri District Hospital: Optimalisasi Pencatatan Digital Sebagai Alat Pemantauan Kinerja SDM Non ASN di Rumah Sakit Kabupaten Kediri - Wulyatie, Larasati; Apriliansyah, Udin; Arifin, Zainal; Prameswari, Dyah; Nurcholis, Nurcholis (Universitas Haji Sumatera Utara, 2025)
The health sector is the main focus of the government. Hospitals as public institutions in the field of health services have great potential to be integrated with information technology. Human resource management in hospitals faces the challenges of task complexity and high job demands. Monitoring HR performance can be done manually or by an application system, but some hospitals still use manual methods. Kediri Regency Hospital (RSKK) is a type B hospital with 925 employees, where the performance monitoring of Non-ASN employees is still manual. This study aims to analyze the factors that cause the suboptimal digital recording as a tool to monitor human resource performance at RSKK. This study uses a descriptive qualitative approach with observation, interview, and documentation techniques. Triangulation of sources is used to check the validity of the data. Data analysis includes data reduction, data presentation, and drawing conclusions based on research findings. The results of this community service activity show that RSKK already has SIMPEG, but it is not optimal with manual non-ASN performance recording. and found 3 problems that need to be considered, namely: There is no workflow and procedures related to digital recording of health HR performance, policies and regulations related to the use of the system have not been optimal, and monitoring and evaluation of health HR performance is not optimal. Problem-solving interventions are needed through SWOT analysis. The SO strategy in the I-Aggressive Strategy quadrant was applied, resulting in a final score of SW 1.61 and O-T 1.72. This condition shows the great strength and opportunity for optimizing digital recording as a tool for monitoring human resource performance.